PENERAPAN KARTU FONIK BERGAMBAR UNTUK MENINGKATKAN PENGUASAAN HURUF DAN BUNYI BAHASA INDONESIA DI SEKOLAH ANSORIAH ADDENEYAH - Khairunisya, Nurul; Febriyana, Mutia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the ability to master Indonesian letters and sounds in Thai students through the application of picture phonics cards in class Matayum 3 Ansoriah Addeneyah School, Thailand. The method used is Classroom Action Research (CAR) with two cycles, where each cycle includes the stages of planning, implementation, observation, and reflection. The research subjects consisted of 10 Thai students, with data collection through tests, observation, and documentation. The results of the study showed a significant increase in the ability to master Indonesian letters and sounds, especially in the aspects of recognizing letters, pronouncing letter sounds, and understanding letter-sound relationships. These findings confirm that the application of picture phonics cards is effective in improving the mastery of Indonesian letters and sounds in Thai students.